Perampingan Birokrasi - Ajib Rakhmawanto (Jurnal Manajemen Kepegawaian, 2021)
The purpose of the analysis of this study is to analyze the policy of bureaucratic simplification and its impact on the equalization of administrative positions (Administrator and Supervisor). This study uses a descriptive analysis approach to explain and analyze bureaucratic downsizing and its impact on equalizing administrative positions. The study data used in the form of literature studies. The results of the analysis of the study show that the simplification of the bureaucracy has not been implemented effectively. The impact on equalizing administrative positions into functional positions still overrides merit aspects (qualifications and competencies). The majority of Administrative Officers who are transferred to Functional Positions do not meet the educational requirements and competencies required for the Functional positions to be occupied.